A novel role for peptidylarginine deiminases in microvesicle release reveals therapeutic potential of PAD inhibition in sensitizing prostate cancer cells to chemotherapy. Issue 1 (22nd June 2015) - Kholia, Sharad; Jorfi, Samireh; Thompson, Paul R.; Causey, Corey P.; Nicholas, Anthony P.; Inal, Jameel M.; Lange, Sigrun
Abstract : Introduction: Protein deimination, defined as the post‐translational conversion of protein‐bound arginine to citrulline, is carried out by a family of 5 calcium‐dependent enzymes, the peptidylarginine deiminases (PADs) and has been linked to various cancers. Cellular microvesicle (MV) release, which is involved in cancer progression, and deimination have not been associated before. We hypothesize that elevated PAD expression, observed in cancers, causes increased MV release in cancer cells and contributes to cancer progression. Background: We have previously reported that inhibition of MV release sensitizes cancer cells to chemotherapeutic drugs. PAD2 and PAD4, the isozymes expressed in patients with malignant tumours, can be inhibited with the pan‐PAD‐inhibitor chloramidine (Cl‐am). We sought to investigate whether Cl‐am can inhibit MV release and whether this pathway could be utilized to further increase the sensitivity of cancer cells to drug‐directed treatment. Methods: Prostate cancer cells (PC3) were induced to release high levels of MVs upon BzATP stimulation of P2X7 receptors. Western blotting with the pan‐protein deimination antibody F95 was used to detect a range of deiminated proteins in cells stimulated to microvesiculate. Changes in deiminated proteins during microvesiculation were revealed by immunoprecipitation and immunoblotting, and mass spectrometry identified deiminated target proteins with putative roles in microvesiculation. Conclusion: We report for the first time a novel function of PADs in the biogenesis of MVs in cancer cells. Our results reveal that during the stimulation of prostate cancer cells (PC3) to microvesiculate, PAD2 and PAD4 expression levels and the deimination of cytoskeletal actin are increased. Pharmacological inhibition of PAD enzyme activity using Cl‐am significantly reduced MV release and abrogated the deimination of cytoskeletal actin. We demonstrated that combined Cl‐am and methotrexate (MTX) treatment of prostate cancer cells increased the cytotoxic effect of MTX synergistically. Refined PAD inhibitors may form part of a novel combination therapy in cancer treatment.